Usability evaluation of the “Teen ‘n Fit” mobile health application: A formative study among Indonesian adolescent girls - Dwi Sisca Kumala Putri; Kencana Sari; Nur Handayani Utami; Nazarina Nazarina; Tiara Amelia; Nadira Yuthie Salwa; Ning Sulistiyowati; Adindra Vickar Ega; Muhammad Azzumar; Rika Rachmawati; Salimar; Mieska Despitasari; et al. (PLoS ONE, 2025)
Background Mobile Health (mHealth) Applications offer a promising approach to promote the adoption of healthy nutrition and behavior among adolescent girls. A tailored mobile app, Teen ‘n Fit, was developed to support adolescent girls in Indonesia to assess their nutritional status, physical activity, and eating behavior; as a nutrition education media; and as a reminder of iron folic acid consumption. However, it is essential to measure the app’s usability prior to the release. Objective This study aimed to measure the usability of a mobile application designed to promote nutrition and healthy behavior of adolescent girls by modifying the mHealth App Usability Questionnaire (MAUQ). Methods A cross-sectional usability study was conducted on 64 adolescent girls aged 15–18 from a public high school in Depok, Indonesia. Participants completed app-based tasks and filled out a post-task usability questionnaire. The usability questionnaire was adapted from a validated MAUQ for a standalone mHealth app. The exploratory factor analysis was conducted to determine the items constituting each component in the modified MAUQ. Mann-Whitney analysis was employed to analyze the difference in usability score means based on participants’ characteristics. Results The modified MAUQ demonstrated strong reliability (Cronbach’s alpha = 0.945). The app achieves a strong usability score, 6.0 ± 0.8 out of 7, with 79.7 percent of participants reporting no prior mHealth experience. The score among participants who occasionally used mHealth applications was higher (p = 0.046) than those who had never made prior use. Conclusion The findings indicate strong usability potential of Teen ‘n Fit as a digital health promotion tool for adolescent girls; however, future efforts in conducting effectiveness tests and maintaining user engagement are needed.